Perubahan Perilaku Penggunaan Alat Pelindung Diri (APD) Pasca Terinfeksi COVID-19 pada Dokter di Indonesia: Sebuah Survei Nasional pada Awal Pandemi - Herikurniawan, Herikurniawan; Yunihastuti, Evy; Syam, Ari F; Soemarko, Dewi Sumaryani Sumaryani; Wiraguna, Andrian (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. Doctors have greater risk of acquiring COVID-19 due to occupational exposure. Personal protective equipment (PPE) is an essential factor in reducing COVID-19 transmission. We aimed to evaluate the behavior changes of PPE usage among doctors in Indonesia before and after getting COVID-19 infection in early pandemic. Methods. This was a descriptive online survey with cross-sectional design. This survey was conducted from October-December 2020 among Indonesian doctors who were COVID-19 survivors. Results. A total of 389 doctors who survived COVID-19 infection across Indonesia were included in the final analysis. Most participants were general practitioners and residents (69.2%) with a median age of 40 (22-28) years. After being infected, there was an improvement in the use of N95 respirator masks in isolation rooms (always: 80.9% from 70.2%; sometimes: 13.2% from 15.8%). An improvement in the use of other PPE before and after being infected with COVID-19 was also shown by the use of other PPE such as headcap (93.9% from 83.3%), face shield (90.4% from 83.3%), goggles (70.2% from 62.3%), gown (61.4% from 53.6%), hazmat suit (88.6% from 81.6%), boots (82.5% from 71.1%), and gloves (91.3% from 86.8%). Similar results were also shown in the use of PPE in other non-isolation rooms. Conclusion. After recovering from COVID-19 infection, these doctors showed an increase usage of adequate PPE both while on duty in isolation and non-isolation rooms.